Examples for the application of rule-based algorithms in the simulation modeling of the physical separation of automated guided vehicles - Skapinyecz, Róbert (Advanced Logistic Systems - Theory and Practice, 2023)
Nowadays, in parallel with the rapid spread of modern automation and digitalization solutions, different autonomous systems are playing an increasingly important role in the field of industry and logistics, a classic example of which is the case of automated guided vehicles (AGVs). Although these devices have been in use for a long time in the aforementioned areas, at the same time, in parallel with the progress of automation in the recent period, in many cases they can be seen more and more as autonomous mobile robots (AMRs), which perform the tasks assigned to them with a high degree of independence. At the same time, issues such as the problem of preventing collisions between individual freely moving vehicles in industrial environments naturally come to the fore. The purpose of this publication is to provide an example for the structure of some simpler rule-based algorithms in response to the former question, which may be relevant in terms of avoiding some potential collision situations of lower complexity. The operation of the algorithms was represented using the Siemens Tecnomatix Plant Simulation discrete event simulation software.